2006
DOI: 10.1007/s10344-006-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of introduced European fallow deer (Dama dama dama) in Tasmania, Australia

Abstract: European fallow deer are an introduced species classified as partly protected wildlife in Tasmania, Australia. Current management practices are primarily governed under the Quality Deer Management regime, in which animals are harvested during designated hunting seasons. Among populations, prominent morphological differences have been reported; however, the genetic relationship of these populations has until now been poorly understood. Representative animals were sampled from three key areas across their range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 54 publications
3
22
0
1
Order By: Relevance
“…This is similar to the results obtained by other authors who documented the genetics of introduced rusa deer in Australia (Webley et al 2004(Webley et al , 2007, as well as other deer species re-introduced in other parts of the world (e.g., DeYoung et al 2003). However, although both wild and domestic sub-populations in New-Caledonia revealed genetic signatures of a bottleneck, probably the same that occurred in 1872 with the introduction of 12 individuals, both the genetic diversity and the structure of the two population groups (farmed and wild) are quite contrasted.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is similar to the results obtained by other authors who documented the genetics of introduced rusa deer in Australia (Webley et al 2004(Webley et al , 2007, as well as other deer species re-introduced in other parts of the world (e.g., DeYoung et al 2003). However, although both wild and domestic sub-populations in New-Caledonia revealed genetic signatures of a bottleneck, probably the same that occurred in 1872 with the introduction of 12 individuals, both the genetic diversity and the structure of the two population groups (farmed and wild) are quite contrasted.…”
Section: Discussionsupporting
confidence: 94%
“…The consequences of bottlenecks may include the loss of rare alleles, followed by the reduction in the mean number of alleles and heterozygosity, the fixation of deleterious alleles, and potentially inbreeding depression. However, although the reduction of genetic diversity has been demonstrated by molecular data for several deer populations that experienced founder effects (e.g., Broders et al 1999;Webley et al 2004Webley et al , 2007 other instances such as the white-tailed deer reintroduction in Mississippi (DeYoung et al 2003) were not associated with a significant reduction in genetic diversity. On the other hand, genetic diversity of farmed animal populations is commonly shaped by human activities.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, vegetation management using mechanical slashing did not alter habitat use by hog deer (Davis et al 2016). The influence of ecological and physiological limits, geographical barriers (Webley et al 2007), drought, climate change, land-use patterns, predation (including hunting) and disease on expansion of Australian deer populations remains unknown.…”
Section: Current and Potential Distributions Of Deer In Australiamentioning
confidence: 99%
“…This finding suggests that genetic monitoring of populations undergoing reintroductions and translocations should be carried out not just prior to intervention, but also afterwards as part of long-term monitoring to assess the genetic impacts of population management. Webley et al (2007) detected two genetically distinct clusters in an introduced population of European fallow deer (Dama dama dama) in Tasmania; as such, the authors recommended that migration between the two clusters be encouraged to promote gene flow. Importantly, although our study has shown how gene flow has been promoted in the Mauritius parakeet as a consequence of management, these actions were motivated by a need to increase productivity rather than to promote genetic mixing.…”
Section: Discussionmentioning
confidence: 97%